2017
DOI: 10.5271/sjweh.3690
|View full text |Cite
|
Sign up to set email alerts
|

Time course of neck-shoulder pain among workers: A longitudinal latent class growth analysis

Abstract: Knowledge about the time course of neck-shoulder pain (NSP) among workers is sparse. Latent class growth modeling was used to distinguish NSP trajectories based on repeated measurements over one year. Six distinct pain trajectories were identified. Pain characteristics, personal and occupational factors predicted severe persistent NSP. The study contributes with novel information about the time course of NSP among workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 30 publications
3
14
0
Order By: Relevance
“…Stock et al studied students from seven different countries and confirmed the results of this study that women are more likely to develop musculoskeletal disorders in the neck [43]. The results of this study were approved for both students and the general population in longitudinal studyies [44][45][46]. In line with the results of this study, Dianat et al highlighted the difference between male and female students in the report of neck pain [47].…”
Section: Discussionsupporting
confidence: 83%
“…Stock et al studied students from seven different countries and confirmed the results of this study that women are more likely to develop musculoskeletal disorders in the neck [43]. The results of this study were approved for both students and the general population in longitudinal studyies [44][45][46]. In line with the results of this study, Dianat et al highlighted the difference between male and female students in the report of neck pain [47].…”
Section: Discussionsupporting
confidence: 83%
“…Based on model fit indices (BIC, entropy and BLRT) and distinction between classes obtained from consecutive LCGA models, a six-class solution was chosen 30. The growth pattern and prevalence (%) of the six identified trajectory classes of NSP were characterised as follows (see also online supplementary figure A): class 1, asymptomatic (11%); class 2, very low NSP (10%); class 3, low recovering NSP (18%); class 4, moderate fluctuating NSP (28%); class 5, strong fluctuating NSP (24%) and class 6, severe persistent NSP (9%).…”
Section: Resultsmentioning
confidence: 99%
“…Theoretical assumptions and empirical evidence were used to select possible confounders and effect modifiers which were accounted for in the statistical analyses. The following variables were measured at baseline as previously described30: age (years) and gender (male or female) based on civil registration number, body mass index (BMI) based on objectively measured height and weight, occupational sector (manufacturing, cleaning, transportation and administration/office work within the same workplaces) and seniority in the current job (years). Physical work load was measured by the question ‘How physically demanding do you normally consider your present work?’ using a 10-point (1–10) response scale modified from Borg,40 with higher values indicating higher physical demands.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations